Investigation of nosocomial SARS-CoV-2 transmission from two patients to healthcare workers identifies close contact but not airborne transmission events. (3rd September 2021) - Bays, Derek J.; Nguyen, Minh-Vu H.; Cohen, Stuart H.; Waldman, Sarah; Martin, Carla S.; Thompson, George R.; Sandrock, Christian; Tourtellotte, Joel; Pugashetti, Janelle Vu; Phan, Chinh; Nguyen, Hien H.; Warner, Gregory Y.; et al.
Abstract: Objective: To describe the pattern of transmission of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) during 2 nosocomial outbreaks of coronavirus disease 2019 (COVID-19) with regard to the possibility of airborne transmission. Design: Contact investigations with active case finding were used to assess the pattern of spread from 2 COVID-19 index patients. Setting: A community hospital and university medical center in the United States, in February and March, 2020, early in the COVID-19 pandemic. Patients: Two index patients and 421 exposed healthcare workers. Methods: Exposed healthcare workers (HCWs) were identified by analyzing the electronic medical record (EMR) and conducting active case finding in combination with structured interviews. Healthcare coworkers (HCWs) were tested for COVID-19 by obtaining oropharyngeal/nasopharyngeal specimens, and RT-PCR testing was used to detect SARS-CoV-2. Results: Two separate index patients were admitted in February and March 2020, without initial suspicion for COVID-19 and without contact or droplet precautions in place; both patients underwent several aerosol-generating procedures in this context. In total, 421 HCWs were exposed in total, and the results of the case contact investigations identified 8 secondary infections in HCWs. In all 8 cases, the HCWs had close contact with the index patients without sufficient personal protective equipment. Importantly, despite multiple aerosol-generating procedures, there was no evidence of airborne transmission. Conclusion: These observations suggest that, at least in a healthcare setting, most SARS-CoV-2 transmission is likely to take place during close contact with infected patients through respiratory droplets, rather than by long-distance airborne transmission.